Opinion 2434: Chionobas chryxus Doubleday, 1849 (currently Oeneis chryxus; Insecta, Lepidoptera, Nymphalidae): conservation of usage by designation of a neotype not granted - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has declined to use its plenary power to set aside the existing lectotype of Chionobas chryxus Doubleday, 1849 and to designate a neotype. However, the International Commission on Zoological Nomenclature has used its specific powers to confirm that the name-bearing type is the male specimen illustrated in Doubleday (1849).
Keywords: Nomenclature; taxonomy; Insecta; Lepidoptera; Nymphalidae; Oeneis; Oeneis chryxus; Oeneis calais altacordillera; nymphalid butterfly; Rocky Mountains